THE EFFECT OF MARKETING STRATEGY AND SERVICE QUALITY ON CUSTOMER SATISFACTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Gultom, Dedek Kurniawan; Harianto, Sheila Anggita (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The increasingly competitive logistics industry in Indonesia requires freight forwarding companies to implement effective marketing strategies and consistent service quality. PT. Anugerah Indo Maritim Sejahtera (AIMS) faces challenges in maintaining customer satisfaction, as indicated by dissatisfaction due to less optimal marketing strategies and inconsistent service quality, which weakens its brand image. This study aims to analyze the influence of marketing strategy on customer satisfaction, the influence of service quality on customer satisfaction, the effect of marketing strategy on brand image, the influence of service quality on brand image, the impact of brand image on customer satisfaction, and the mediating role of brand image in the relationship between marketing strategy, service quality, and customer satisfaction at PT. AIMS. The research adopts a quantitative associative method involving 100 respondents selected through total sampling. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Square (SmartPLS) to test seven hypotheses. The results indicate that both marketing strategy and service quality have a positive and significant effect on customer satisfaction and brand image. Furthermore, brand image significantly influences customer satisfaction and mediates the relationship between marketing strategy, service quality, and customer satisfaction. These findings highlight that the combination of effective marketing strategies and high-quality services builds a strong brand image, which directly enhances customer satisfaction.